(untitled) (Tribhuvan University Journal of Microbiology, 2024)
Objectives: The study aims to determine the antibiotic susceptibility pattern of extended spectrum beta-lactamase (ESBL)-producing isolates of Klebsiella and Pseudomonas from clinical specimens. Methods: A total of 230 samples from different bodily fluids (urine, sputum, drain, pus, BAL, CSF, blood, and ascitic fluid) of patients were collected from various wards of Alka Hospital Private Limited, Lalitpur, Nepal. The samples were analyzed in the microbiological laboratory as per the CLSI guidelines. The Kirby-Bauer disc diffusion technique.was used to perform antibiotic susceptibility testing. Results: Thirty-four (14.78%) samples showed culture positivity. Urine had the highest culture positivity; the patients of the age group 90-100 years were 66.67% culture positive. 100% of the samples from the SH/C ward were culture-positive. Of 34 isolates, 88.24% were ESBL producers, including 61.76% K. pneumoniae, 11.76% K. oxytoca, and 26.47% P. aeruginosa. MDR was observed in 96.3% of ESBL producers. Amikacin, Gentamicin, and Piperacillin-tazobactam were the most effective against ESBL-producing P. aeruginosa. Colistin and Polymyxin-B were the most effective antibiotics against Klebsiella species. Conclusion: The study reports ESBL production significantly affected MDR development in selected bacterial specimens.